1976
DOI: 10.1254/jjp.26.711
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Cyclic Nucleotides in the Adrenal Gland V. Adenylate Cyclase in the Adrenal Medulla

Abstract: Abstract-Effects of various chemical agents eliciting the catecholamine-release on the adenylate cyclase-cyclic AMP generating system have been studied in the secretory process of the bovine adrenal medulla slices. Cyclic AMP levels were not affected at the interval of the maximal increase of the catecholamine-release by acetylcholine, but increased gradually some time after the end of the release/or at the beginning of the restoration of catecholamine in the medulla tissue. This delayed increase in the medull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…In the present study using bovine cultured chromaffin cells, we found a reproducible cellular cyclic AMP response to nicotine, DMPP and acetylcholine, although as noted by others (Tsujimoto et al, 1980;Morita et al, 1987), this reponse was transient: at times longer than Shima et al (1976) found they needed periods longer than 20 min before they saw any cyclic AMP response. However, they used slices of bovine adrenal medulla, which may only allow slow penetration of agonists into the tissue.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In the present study using bovine cultured chromaffin cells, we found a reproducible cellular cyclic AMP response to nicotine, DMPP and acetylcholine, although as noted by others (Tsujimoto et al, 1980;Morita et al, 1987), this reponse was transient: at times longer than Shima et al (1976) found they needed periods longer than 20 min before they saw any cyclic AMP response. However, they used slices of bovine adrenal medulla, which may only allow slow penetration of agonists into the tissue.…”
Section: Discussionsupporting
confidence: 75%
“…Cholinoceptor-mediated cyclic AMP responses in adrenal medullary cells Previous studies have found conflicting evidence on the ability of cholinoceptors to increase cyclic AMP levels in chromaffin cells. A number of authors found that carbachol or acetylcholine had no effect on adenylate cyclase activity in membranes prepared from bovine adrenal medulla (Serck-Hanssen et al, 1972;Hurko et al, 1974;Boonyaviroj & Gutman, 1977) while others found no effect of carbachol, acetylcholine, nicotine or DMPP on cyclic AMP levels in slices or isolated cells from this tissue (Shima et al, 1976;Niggli et al, 1984;Chern et al, 1988;Marriott et al, 1988). In contrast, several reports have recorded robust cyclic AMP responses to cholinoceptor agonists in slices of bovine adrenal medulla or in cultured bovine chromaffin cells (Shima et al, 1976;Eiden et al, 1984;Morita et al, 1987;Wilson, 1988).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although histamine has been shown previously to induce CA release from bovine adrenal medulla (Schneider, 1969;Shima et al, 1976) (Figure 4b). Histamine when administered intravenously to anaesthetized animals has been reported to release Ad selectively from the intact adrenal gland of the cat (StaszewskaBarczak & Vane, 1965) the dog (Schaepdryver, 1959;Narita, 1971), and the rat (Z. Khalil, Marley & Livettunpublished observations).…”
Section: Discussionmentioning
confidence: 73%